Screen-based behaviour in school-aged children with long-term illness - Husarova, Daniela; Geckova, Andrea Madarasova; Blinka, Lukas; Sevcikova, Anna; van Dijk, Jitse P; Reijneveld, Sijmen A (BMC public health, 2016)
BACKGROUND: Evidence is lacking on the screen-based behaviour of adolescents with a chronic condition. The aim of our study was to analyse differences in screen-based behaviour of adolescents by long-term illness, asthma and learning disabilities. METHODS: We used data from the cross-sectional Health Behaviour of School-aged Children study collected in 2014 among Slovak adolescents (age 13 to 15 years old, N = 2682, 49.7 % boys). We analysed the associations between screen-based behaviour and long-term illness, asthma and learning disabilities using logistic regression models adjusted for gender. RESULTS: We found no associations between screen-based behaviour and long-term illness, except that children with asthma had a 1.60-times higher odds of excessively playing computer games than healthy children (95 % confidence interval of odds ratio (CI): 1.11-2.30). Children with learning disabilities had 1.71-times higher odds of risky use of the Internet (95 % CI: 1.19-2.45). CONCLUSION: Adolescents with a long-term illness or with a chronic condition or a learning disability do not differ from their peers in screen-based activities. Exceptions are children with asthma and children with learning disabilities, who reported more risky screen-based behaviour.
Keywords: logistické modely; Asthma; bronchiální astma; Humans; Sedentary Behavior; televize; Chronic Disease; Female; poruchy učení; Ethnicity; sedavý životní styl; zdravé chování; lidé; Slovakia; Slovenská republika; počítače; Computers; internet; ženské pohlaví; Video Games; Internet; Male; Television; chronická nemoc; Adolescent; Odds Ratio; Cross-Sectional Studies; Learning Disabilities; etnicita; videohry; mužské pohlaví; odds ratio; průřezové studie; Logistic Models; mladiství; Health Behavior